Evaluating the effectiveness of ISo 14001-environmental management system (EMS) in improving key environmental performance indicators of Eskom distribution : a case study of Mpumalanga operating unit - Van Aardt, I. (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2019.